Acupuncture is clinically but not yet cost‐effective in the treatment of symptomatic idiopathic detrusor overactivity. Issue 2 (31st July 2018) - Jenks, Julie; Kavia, Rajesh; Pakzad, Mahreen H.; Hamid, Rizwan; Ockrim, Jeremy L.; Greenwell, Tamsin J.
Abstract : Is acupuncture clinically and cost‐effective in the treatment of symptomatic idiopathic detrusor overactivity (IDO)? To assess the symptomatic outcome of patients having acupuncture for IDO and to assess and compare costs with other common IDO treatments. Acupuncture is well‐tolerated and produces a significant short‐term reduction in frequency and urgency in patients with overactive bladder (OAB). Repeat treatments are required for continued benefit. Thirty patients having acupuncture for symptomatic IDO were prospectively evaluated using objective (frequency/volume chart) and subjective (EurQol 5 dimension 3 level (EQ5D‐3L), International consultation on incontinence questionnaire on overactive bladder (ICIQ‐OAB), pain scores) measures. Outcome measures were assessed at baseline and post‐treatment, and compared for responders and non‐responders. A cost analysis was performed comparing acupuncture with mono and duel drug pharmacotherapies commonly used in OAB and conservative management methods. Statistical analysis was by Student's paired t test for parametric and Mann‐Whitney U test for non‐parametric data. Of the 30 patients 27 (90%) patients completed treatment with no reported adverse effects. OAB symptoms were "cured" in 14.8%, significantly improved in 59.3% and unchanged in 25.9%. Responders had a significantly lower mean pretreatment functional capacity compared with non‐responders and had a significant increase in this capacity following treatment. Acupuncture carried a higher cost burden at 6 months (£2267/2990/€2560) compared to pharmacotherapy (mono = £477/590/€539) or (duel = £681/898/€769) and conservative methods (£749/988/€846). Acupuncture is a well‐tolerated and effective treatment for IDO and should be part of the clinical armamentarium in a comprehensive continence service. It is more costly than maximal pharmacotherapy and conservative methods but has excellent compliance.